The Scholarly Publication: What and Where [In Bulgarian] - B.V. Toshev (University of Sofia, 2013)
The present paper addresses the old-age problems in scholarly publishing as well as the new challenges resulting from the contemporary changes both of the status of science and also in technology and funding. In the paper the ways to get effectively published in world primary research journals are shown. The role of the second level (secondary sources) of the world system of abstracting, indexing and evaluation is clarified. Some problems of the scientometrics are discussed. Who are the authors - scientists or dilettantes: the differences between these two groups are listed.